Beyond Control: Accessioning Practices for Extensible Archival Management. Issue 3 (2nd October 2017) - Searcy, Rachel
Abstract: Accessioning has long been one of our profession's least visible, discussed, and critically examined activities. This article analyzes our scholarly literature on the subject, revealing an absent theoretical framework and a marked over-reliance on static assumptions about what accessioning entails, to the detriment of both archivists and our collections. The case study that follows describes the creation of an accessioning program at New York University and posits a model of accessioning situated in the context of holistic archival administration, based on both theory and practice, and informed by access-driven workflows and iterative processing strategies.